Agreeing to disagree? Explaining self–other disagreement on leadership behaviour. Issue 12 (2nd December 2019) - Vogel, Dominik; Kroll, Alexander
ABSTRACT: Leadership research tends to treat differences among ratings of the same leaders as measurement error. Our study makes such varying perceptions of leadership behaviour its main phenomenon of investigation. We conceptualize divergent leadership ratings based on the difference between managers' self-ratings and team members' assessments of leadership behaviour. Using data from three German public organizations on 51 teams and 190 leader–follower dyads, we find that divergent leadership ratings are a function of managers' motivation, their use of managerial reflection routines, and team members' personality. The findings point to the importance of using multisource feedback and developing managers' self- and other-awareness.